1981
DOI: 10.1902/jop.1981.52.6.328
|View full text |Cite
|
Sign up to set email alerts
|

Activated Macrophages in Human Periodontitis

Abstract: Fifteen patients, eight males and seven females, ranging from 30 to 88 years of age with advanced periodontal disease were selected for this study. Biopsies and blood samples were taken of both normal and inflamed gingival tissues, and processed for detection of nonspecific esterase and acid phosphatase activity in monocytes and macrophages. Activated macrophages, as indicated by their intense reaction to acid phosphatase and nonspecific esterase, were found in the gingival epithelium, lamina propria, perivasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…In this study, we selected macrophages because macrophagemediated inflammatory response plays a crucial role in development of periodontal disease (Charon et al 1981;Shapira et al 1996;Jagannathan et al 2014). Results showed that LPS induced IL-6 secretion from bone marrow-derived macrophages, while PA had no effect, although it did enhance the stimulatory effect of LPS by 2-fold (Fig.…”
Section: Hfd Enhances Lps-stimulated Cytokine Expressionmentioning
confidence: 99%
“…In this study, we selected macrophages because macrophagemediated inflammatory response plays a crucial role in development of periodontal disease (Charon et al 1981;Shapira et al 1996;Jagannathan et al 2014). Results showed that LPS induced IL-6 secretion from bone marrow-derived macrophages, while PA had no effect, although it did enhance the stimulatory effect of LPS by 2-fold (Fig.…”
Section: Hfd Enhances Lps-stimulated Cytokine Expressionmentioning
confidence: 99%
“…However, there have been an increasing number of papers describing macrophages in various inflammatory tissues such as lung [9,10], gingi val tissue [11], subcutaneous wounds [12] and skin [13]. Participation of alveolar macrophages in derangement of interstitial collagen in idiopathic pulmonary fibrosis [9], participation of activated alveolar macrophages from smokers in injured lung parenchyma [10], and, on the contrary, participation in wound repair by contribution to fibroplasia, collagen synthesis and angiogenesis [12], were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Participation of alveolar macrophages in derangement of interstitial collagen in idiopathic pulmonary fibrosis [9], participation of activated alveolar macrophages from smokers in injured lung parenchyma [10], and, on the contrary, participation in wound repair by contribution to fibroplasia, collagen synthesis and angiogenesis [12], were reported. In gingival tissue, it was suggested that activated macrophages indicated not only an attempt to remove the irritants, but also their participation in de struction of the periodontium through the release of lysosomal enzymes [11],…”
Section: Discussionmentioning
confidence: 99%
“…Although neutrophils and lymphocytes are important cells in the pathogenesis of PD [21, 85] roles for other immune cells such as MØ are less well understood [8688]. MØ comprise between 5–30% of the inflammatory cells identified in PD lesions [89].…”
Section: Macropahges As Effectors At the Microenvironmental Levelmentioning
confidence: 99%